TANGGUNG JAWAB KONTRAKTOR DALAM PERBEDAAN SPESIFIKASI PENGGUNAAN BAHAN BANGUNAN DARI YANG DIPERJANJIKAN - Ary Ananda Putra, I Made; Wiryawan, I Wayan; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2015)
Legal relationship between the contractors with the clients stated in the agreement that bindsthe parties. The aims of this research are the basic demands for compensation by the client to thedifferences in the specifications of building materials used by the contractor and the contractoraccountable for any losses suffered by the client due to the different specifications of the buildingmaterials. Type of research is a normative juridical through statute approach and legal conceptanalysis approach. Legal material that has been collected analyzed through description,construction law, argumentation and systematization techniques. Filed claims for compensationbased on the default of the content of the agreement. Responsibilities carried out by the contractor topay compensation in accordance with the agreed despite losses caused by the deliberate action ofthe field operators and / or field supervisor.
Keywords: Responsibility, contractor, tort, compensation